GENDER EQUALITY IN THE DIVISION OF SPOUSAL ROLES: AN ISLAMIC JURISPRUDENTIAL ANALYSIS OF THE CONCEPT OF PROPORTIONAL JUSTICE - Hudzaifah Ibnu Ahmad; Syafiq Riza Hasan (Journal Analytica Islamica, 2026)
The concept of gender equality often raises issues in the division of household tasks and responsibilities, especially when confronted with Islamic jurisprudence, which generally establishes functional roles for husbands and wives. This study aims to analyze Islamic views on gender equality, detail the diversity of jurisprudential views (ikhtilaf) regarding the division of roles between husband and wife, and examine the application of gender equality principles in household management. This research uses a library research method with a qualitative approach, collecting data from cross-madhhab fiqh literature, interpretations, and scientific articles. The results show that Islam promotes the principle of proportional justice (equity, i.e., the balanced fulfillment of rights and obligations according to capacity) while acknowledging equal human value (equality before the Sharia). Role differentiation is based on biological and psychological fitrah (innate characteristics of creation), rather than absolute kodrat (rigid determinism), thereby avoiding the creation of a hierarchy of values. While the majority of scholars establish the husband as the leader (qawwam) and main breadwinner, and the wife as the primary manager of the household, Islamic jurisprudence also recognizes flexibility and diverse perspectives regarding women's public roles and household management through the principles of mutual consultation (musyawarah) and benefit (maslahah). This division is positioned as a functional differentiation. In conclusion, the application of gender equality aligns with Islam if interpreted as proportional justice that considers the fitrah of each individual, rather than a rigid division that ignores the diversity of Sharia perspectives and the actual conditions of the family.